2019
DOI: 10.1007/s12034-019-1826-0
|View full text |Cite
|
Sign up to set email alerts
|

A spring network simulation in three dimensions for designing optimal crack pattern template to fabricate transparent conducting electrodes

Abstract: Desiccation cracks in colloids are of the order of µm width or less. Therefore, such connected crack networks in a desiccating colloidal film can provide a very fine template for the fabrication of transparent conducting surfaces by vapour deposition of a metal onto the crack network (Rao et al 2014 Adv. Mater. Interfaces 1 140009). The colloidal layer is removed leaving a connected metallic network invisible to the eye. So the surface becomes conducting, while retaining its transparency. The challenge lies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is found that the experimentally obtained crack pattern with time goes well with the predicted time evolution of cracks. Furthermore, the simulated patterns of cracks using spring fusion-based modeling 26 also possess the widening of cracks, strengthening the proposed assumption. In the spring fusion model, the film is represented as a cuboidal lattice with nodes representing the particles and Hookean springs connecting the nearest neighbors representing the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the experimentally obtained crack pattern with time goes well with the predicted time evolution of cracks. Furthermore, the simulated patterns of cracks using spring fusion-based modeling 26 also possess the widening of cracks, strengthening the proposed assumption. In the spring fusion model, the film is represented as a cuboidal lattice with nodes representing the particles and Hookean springs connecting the nearest neighbors representing the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we demonstrated cracking at tapered edges between pyramids to prepare microscale pyramidal particles in the previous work . The relationship between the film thickness and the cracked area or the spacing between fragments ,, has been studied experimentally, theoretically, , and by simulations . This relationship can be used to predict paint film thicknesses in ancient paintings or to understand desiccation patterns in sessile blood drops. , …”
Section: Introductionmentioning
confidence: 90%
“…28 The relationship between the film thickness and the cracked area or the spacing between fragments 5,19,29 has been studied experimentally, 30−32 theoretically, 29,33 and by simulations. 34 This relationship can be used to predict paint film thicknesses in ancient paintings 35 or to understand desiccation patterns in sessile blood drops. 36,37 In this work, we investigate the effect of notches and film thicknesses by imprinting pyramidal shapes on colloidal films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The cracks thus present geometrical characteristics described by the following parameters: depth, thickness, density, spacing, and aperture. In this way, the crack pattern reveals the mechanical properties of the material 7 and offers a wide variety of applications 8,9 . These patterns have been extensively observed in a variety of materials, such as ceramics, paints or particulate coatings where cracking results from solvent evaporation [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%